2020
DOI: 10.21203/rs.3.rs-15576/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Presentation Intervals and the Impact of Delay on Breast Cancer Progression in a Black African Population

Abstract: BACKGROUND: The help-seeking interval and primary-care interval are points of delays in breast cancer presentation. To inform future intervention targeting early diagnosis of breast cancer, we described the contribution of each interval to the delay and the impact of delay on tumor progression. METHOD: We conducted a multicentered survey from June 2017 to May 2018 hypothesizing that most patients visited the first healthcare provider within 60 days of tumor detection. Inferential statistics were by t-test, chi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Reports of prolonged delay of more than three months are prevalent in Africa, ranging up to 70% compared to 16-17% in Europe and the USA (Innos, Padrik, Valvere, et al, 2013). Breast cancer progression is time-dependent (Fujii et al, 2015;Agodirin et al, 2020); however, the significance of 3 months delay as a predictor of advanced-stage diagnosis was not found in this analysis. The association between delay and advanced stage diagnosis has also not been consistent in African literature; some researchers found an association between long intervals and advanced-stage diagnosis (Brinton et al, 2017) while others did not (Galukande et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Reports of prolonged delay of more than three months are prevalent in Africa, ranging up to 70% compared to 16-17% in Europe and the USA (Innos, Padrik, Valvere, et al, 2013). Breast cancer progression is time-dependent (Fujii et al, 2015;Agodirin et al, 2020); however, the significance of 3 months delay as a predictor of advanced-stage diagnosis was not found in this analysis. The association between delay and advanced stage diagnosis has also not been consistent in African literature; some researchers found an association between long intervals and advanced-stage diagnosis (Brinton et al, 2017) while others did not (Galukande et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…A single study analysis for risk of delay among patients with low BC knowledge (Ayoade et al, 2015) (OR 1.61, 95% CI 1.20-2.17) showed a significant association with delay. Other single studies showed that misinterpreting breast cancer symptoms as breast infection (Grosse et al, 2018) (OR 6.11, 95% CI 1.49-25.1) and having a smaller mass (Agodirin et al, 2020), (OR 1.56, 95% CI 1.0-2.43) were associated with delay.…”
Section: Determinants Of Delayed Presentationmentioning
confidence: 99%